A study on parking characteristics in Bangkok - Afroze, Naveed; Yordphol Tanaboriboon; Fukuda, Atsushi; Mori, Hiroshi; Royal Government of Thailand (Bangkok : Asian Institute of Technology, 1991)
This research deals with the studies on parking characteristics on both on- street and off-street parking facilities in the Bangkok Metropolitan Area. The appendage of on street parking was streamed keeping in view the idea of evaluating the effects of the curb parking ban on the traffic characteristics. To study the effects of the on-street parking ban travel time surveys were carried out at the commercial area of Banglumpoo through the license plate technique and the data were collected at ten locations in the study area encompassing the entire network . In association, the volume counts were also taken to support the results of t h e travel time study. The data so agglomerated were analyzed statistically. Effect on the network of the on-street parking ban was found positive in the sense that the travel time were reduced ranging between 11.00% to 53.37% and also the increment in the traffic volume was evident. The increment in the traffic volume was fluctuating between 0.00% 60.13%. The off-street parking consisted of the study on the physical and the geometrical characteristics of t h e selected car parks. To oblige this objective, six car parks serving different environments and land uses with the design diversity , were selected. The study unfolded the fact that there stands a strong need to revise and replenish the design guidelines furnished by the Bangkok Metropolitan Administration {BMA), especially for t h e parking stall dimensions and the design length of the aisles along with the design criterion for the design of entrances and exits. The behavioral study for the parking time of the parkers was also carried out at two selected car parks one imposing the parking fee and other providing free parking. The study was carried out aided with t h e license plate technique to arrive at the average parking time of the parkers. The statistical tests carried to analyze the data so amassed revealed that t h e parking time at the weekend is longer than the parking time on the weekday. Also this analysis disclosed that there exists no effect of the parking fee on the parking time of the parkers and it is not substantial enough to transform the parking time and the modal choice behavior of the parkers .
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Automobile parking -- Thailand -- Bangkok